Features of Clinical Course of the Processes of Psychophysiological and Mental Adaptation and Topical Issues of Evaluation of Health Status of Schoolchildren - O.P. Mostova (Zaslavsky O.Yu., 2013)
The article describes features of clinical course of the process of psychophysiological and mental adaptation and topical issues of evaluation of health status of schoolchildren. It is found that the most appropriate course of psychophysiological adaptation processes is in girls and boys who have higher level of health as compared with age-mates, without prenosological changes in state of health and any signs of chronic disease. At the same time, estimation of mental adaptation processes determinates fact that in the context of similar past trends for a number of indicators (situational and personal anxiety, etc.), pupils with higher levels of health were more slow and abnormal processes of mental adaptation. The results of investigation clearly and adequately define the fact that the definition of the characteristics of flow processes psychophysiological and mental adaptation is an integral component of implementing a comprehensive health evaluation of pupils of school age and an important prerequisite for developing and implementing individualized in content of health promotion technologies.